Energy Storage in Covalent Organic Frameworks: From Design Principles to Device Integration - Ding, Huimin; Mal, Arindam; Wang, Cheng (Chemical research in Chinese universities, 2022)
C ovalent organic frameworks(COFs) have received profound attention in recent years owing to their tailor-made porosity, large surface area and robust stability. More specifically, 2D COFs with redox-active and π electron-rich units allow efficient charge carriers hopping and ion migration, thus offering great potentials in energy storage. Herein, we present a systematic and concise overview of the recent advances in 2D COFs related to the electrochemical energy field, including supercapacitors, fuel cells, rechargeable lithium batteries, lithium-sulfur batteries, and other metal-ion batteries. In addition, a brief outlook is proposed on the challenges and prospects of COFs as electrode materials for energy storage.